Open Access and Open Data Management Strategy for Phase II (2017-2022): CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
In accordance with the CGIAR Open Access and Data Management Policy (OADM), CCAFS is mandated to produce international public goods and ensure that they are open via FAIR principles – that is, they are Findable, Accessible, Interoperable and Re-usable to enhance innovation, impact, and uptake. CCAFS has developed its Data Management Strategy (DMS) to enable the program to fulfill its obligations with respect to making information and data products supporting documentation from its research globally available.